2013
DOI: 10.1186/1748-5908-8-16
|View full text |Cite
|
Sign up to set email alerts
|

Improving physician hand hygiene compliance using behavioural theories: a study protocol

Abstract: BackgroundHealthcare-associated infections affect 10% of patients in Canadian acute-care hospitals and are significant and preventable causes of morbidity and mortality among hospitalized patients. Hand hygiene is among the simplest and most effective preventive measures to reduce these infections. However, compliance with hand hygiene among healthcare workers, specifically among physicians, is consistently suboptimal. We aim to first identify the barriers and enablers to physician hand hygiene compliance, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 47 publications
1
39
0
Order By: Relevance
“…12 No intervention studies with explicit reference to psychological theories had been published until April 2011, 13 and recent trials have been limited to nurses 14,15 or are still underway. 16,17 Exploratory studies have tended to consider hand hygiene behaviour (HHB) as reasoned actions directly influenced by behavioural intentions. 8,18e20 However, only one study found this effect, and it was limited by a small sample size (N ¼ 104), low response rate (34%) and no differentiation between professional groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 No intervention studies with explicit reference to psychological theories had been published until April 2011, 13 and recent trials have been limited to nurses 14,15 or are still underway. 16,17 Exploratory studies have tended to consider hand hygiene behaviour (HHB) as reasoned actions directly influenced by behavioural intentions. 8,18e20 However, only one study found this effect, and it was limited by a small sample size (N ¼ 104), low response rate (34%) and no differentiation between professional groups.…”
Section: Introductionmentioning
confidence: 99%
“…18 Also, limitations of theories focusing on attitudes have been pinpointed, arguing that HHB is an acquired habit rather than a reasoned action. 13,16,21,22 There are two sides to this 'habitual quality' coin. First, habits tend to presume stable and supportive environments.…”
Section: Introductionmentioning
confidence: 99%
“…Hand hygiene is widely recognised as one of the most successful and cost-effective measures to reduce the incidence of healthcare associated infections (HCAIs) [1][2][3]. Hand hygiene best practice in clinical settings as a key preventive intervention has been endorsed by a number of key organisations including the World Health Organisation, Centers for Disease Control and Prevention, the National Health and Medical Research Council, Australian Commission on Safety and Quality in Health Care and Hand Hygiene Australia.…”
mentioning
confidence: 99%
“…Reasons behind this can lie in limited knowledge of the five moments for HH, a lack of positive role models or simply a lack of interest. So far, barriers to compliance, especially with respect to physician-specific barriers, are poorly understood [11].…”
Section: Introductionmentioning
confidence: 99%